Les processus de (dé)professionnalisation entre savoir, rapport au savoir et contrôle - Philippe Perrenoud (Recherches en Éducation)
The (de)professionalization of teacher’s job is a multidimensional process. The main dimensions are: nature of prescriptions and autonomy at work, reference to a state of the art and knowledge, reference to ethical guidelines, actors’s collective power on their job, control of initial and continuing training, legal responsibilities, professional development, power on the organization and division of labor, method of supervision, accountability, source of control, diversity of tasks, complexity of problems to solve, adaptation to change, mobility, internal and social recognition. These dimensions are interdependent, but that does not exclude asynchonous evolutions or even changes in contradictory directions.Can we identify dominant dimensions, which would drive the process of (de)professionalization? The article sustains the hypothesis that the relationship to the established knowledge and the mode of control of the teacher’work are the dominant dimensions.